Sex-related absolute inequalities in tuberculosis incidence in 47 countries in Africa - Aliu Mohammed; Richard Gyan Aboagye; Precious Adade Duodu; Qorinah Estiningtyas Sakilah Adnani; Florence Gyembuzie Wongnaah; Abdul-Aziz Seidu; Bright Opoku Ahinkorah (BMC Medicine)
Abstract Background Tuberculosis (TB) remains a major infectious disease of public health concern in Africa; understanding the sex disparities in TB burden is crucial for advancing global health objectives in TB diagnosis and treatment. Methods This study assessed the sex-related disparities in the incidence of TB in 47 countries in Africa. Data for the study was obtained from the World Health Organization (WHO) repository, which is incorporated into the Health Equity Assessment Toolkit (HEAT). We used the WHO HEAT software version 3.1 and Stata software version 17.0 for the analysis. We estimated the difference between the TB incidence in males and females as a measure of inequality. Inequality was measured using Difference (D), an absolute summary measure of inequality. Results The study revealed varying degrees of disparities in TB incidence, which skewed towards men in all countries across Africa, encompassing countries with different income levels. Lesotho (D = − 512.07) recorded the highest difference in TB incidence, which skewed towards men. At the income level, the Central African Republic (D = − 257.77), Lesotho (D = − 512.07), and Namibia (D = − 288.12) recorded the highest absolute disparities in the low-income, lower middle-income, and upper middle-income countries, respectively. Meanwhile, Togo (D = − 19.68), Comoros (D = − 17.79), Mauritius (D = − 10.08), and Seychelles (D = − 19.83) recorded the least sex-related disparities in TB incidence in low-income, lower middle-income, upper middle-income, and high-income countries, respectively. Conclusions Interventions aimed at minimising the burden of TB in Africa could be targeted at reducing men’s exposure to TB risk factors. Such interventions could reduce the incidence of TB among men in Africa and contribute towards the achievement of the Sustainable Development Goal three target 3.3, which seeks to end the global epidemics of TB by 2030.